2018
DOI: 10.1177/2058739218762993
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of 18β-glycyrrhetinic acid against inflammation microenvironment in gastric tumorigenesis targeting PGE2-EP2 receptor-mediated arachidonic acid pathway

Abstract: Accumulating epidemiological and clinical evidence shows that inflammation is an important risk factor for gastrointestinal diseases. Glycyrrhiza glabra, a traditional Chinese medicine, has been shown to safely suppress gastric cancer; however, the anti-inflammatory mechanisms in gastric tumorigenesis have been poorly investigated. Therefore, this study is committed to demonstrate the in vivo anti-inflammatory effect of 18β-glycyrrhetinic acid (GRA), the main active component of G. glabra. The lymphocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Glycyrrhetinic acid (GA) 1 is the hydrolyzed metabolite of glycyrrhizin, a major pentacyclic triterpenoid saponin obtained from the roots of licorice ( Glycyrrhiza species) in high yields up to 24% [16,17]. This compound has been shown to inhibit tumor initiation [18,19,20,21,22] and proliferation in several cancer cell lines; its antiproliferative activity is mediated by cell cycle arrest [23,24] and induction of apoptosis [21,25,26,27,28]. The antitumor effects of GA 1 were also observed in animal models [20,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhetinic acid (GA) 1 is the hydrolyzed metabolite of glycyrrhizin, a major pentacyclic triterpenoid saponin obtained from the roots of licorice ( Glycyrrhiza species) in high yields up to 24% [16,17]. This compound has been shown to inhibit tumor initiation [18,19,20,21,22] and proliferation in several cancer cell lines; its antiproliferative activity is mediated by cell cycle arrest [23,24] and induction of apoptosis [21,25,26,27,28]. The antitumor effects of GA 1 were also observed in animal models [20,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Progressively, a similar study on liquorice extract and its phytoconstituents established anti-inflammatory activity by involvement of TNF, PGE2, MMPs and free radicals cascade ( Yang et al, 2017 ). Further, protective effect on gastric tumorigenesis by 18-β-glycyrrhetinic acid was established by anti-inflammatory action through PGE2-EP2 receptor-mediated arachidonic acid pathway ( Cao et al, 2018 ). In another study, two isolates namely isoliquiritigenin and naringenin from liquorice was identified to improve T cells synthesis and regulation involve for anti-inflammatory action ( Tiwari et al, 2018 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%